A piece of me became a little star: an approach on children’s grief (Research, Society and Development, 2021)
Since the beginning of humanity, in various cultures man has been looking for solutions to explain death and alleviate its suffering through science, myths, religions and philosophy. During this process children can present different symptoms in the process of elaboration of grief, such as guilt, fear, anxiety, irritability, anguish, feeling of abandonment, among several other occurrences. This study is a narrative literature review, with a qualitative approach to the facts. The material collection process began with the choice and consultation of key words in DeCS (Descriptors in Health Sciences). After the analysis, a search was made in the SCIELO (Scientific Electronic Library Online), PubMed and Google Scholar databases with the following descriptors: Children, grief, feelings and communication. As main results, it was observed for fear of not knowing how to deal with the children's reaction or in an attempt to stop the suffering, it is quite common for adults to try to restrict them from experiencing grief, avoiding the issue because they also believe that they are too new to understand the dimension of death. However, several authors claim that thinking and acting in such a way is useless, since death is part of a definitive process. Preventing the child from experiencing this moment within the comfort and support of the family can be even more harmful to their development. It is concluded that there is a need for changes within the family scenario in favor of child mourning, it is important that children can be seen and respected as someone likely to suffer from the death of a loved one, and that with a more cautious look, adults can value and care for the feelings of this child, so that this experience is experienced in the least harmful way possible.